Pengaruh Budaya Organisasi, Keterlibatan Kerja dan Persepsi Dukungan Organisasi Terhadap Kepuasan Kerja Karyawan pada Rumah Sakit Permata Pamulang Tangerang Selatan - Zikri, Arian; Rantina, Meilanta (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to find out and analyze the influence of organizational culture, work involvement and perception of organizational support on employee job satisfaction at Permata Pamulang Hospital, both partially and simultaneously. The method used in this study is a quantitative method that is associative. The source of this research is using primary data and secondary data. The sample collection technique used saturated samples, with a total of 50 samples. The data collection technique is to use questionnaires that are distributed directly to employees. The data analysis technique in this study used multiple linear regression analysis with the SPSS 25 program and a significant influence rate of 5% (0.05). The conclusion in this study shows that there is a positive and significant influence of organizational culture on job satisfaction, there is a positive and significant influence of work involvement on job satisfaction, and there is a positive and significant influence of the perception of organizational support on job satisfaction. There was a positive and significant influence of organizational culture, work involvement, and perception of organizational support together on employee job satisfaction at Permata Pamulang Hospital, with an R Square value of 0.726 or 72.6% and the remaining 27.4% was influenced by other variables that were not observed in this study.